Perioperative Transjugular Intrahepatic Portosystemic Shunt Is Associated With Decreased Postoperative Complications in Decompensated Cirrhotics Undergoing Abdominal Surgery. Issue 7 (July 2022) - Aryan, Mahmoud; McPhail, James; Ravi, Sujan; Harris, Patrick; Allamneni, Chaitanya; Shoreibah, Mohamed
Background: Operative risk in patients with cirrhosis is related to the severity of liver disease and nature of procedure. Pre and postoperative portal decompression via transjugular intrahepatic portosystemic shunt (TIPS) are logical approaches to facilitate surgery and improve postoperative outcomes. We compared postoperative outcomes of decompensated cirrhotics undergoing abdominal surgery either with or without perioperative TIPS placement. Methods: We performed a retrospective review of 41 decompensated cirrhotic patients who had abdominal surgery from 2010-2019 at the University of Alabama at Birmingham. Patients were stratified based on having received either perioperative TIPS or no TIPS. Demographics, laboratory data, perioperative TIPS status and postoperative complications were compared between the 2 groups using Fisher exact test and Student 2 sample t-test. Results: Group 1 consisted of 28 patients who had TIPS procedure, with 21 being preoperative and 7 being postoperative. Group 2 had 13 patients who had abdominal surgery without TIPS. When compared to those with perioperative TIPS, patients without TIPS had a significantly increased incidence of postoperative ascites (33% vs 77%, P = .0026), infection (18% vs 54%, P = .028), and acute kidney injury (AKI) (14% vs 46%, P = .0485). Additionally, postoperative Model of End Stage Liver Disease Sodium score was significantly higher in patients without TIPS (22 ± 4.74) when compared to those who had TIPS (17.14 ± 5.48) ( P = .009). Discussion: Perioperative TIPS placement in decompensated cirrhotics was associated with decreased postoperative ascites, infection, and AKI when compared to those without TIPS. Further studies are needed to validate our findings.